2009
DOI: 10.1007/s00586-009-0947-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised study on the long-term effect of lumbar fusion on adjacent disc degeneration

Abstract: The existence and importance of an accelerated adjacent segment disc degeneration (ASD) after lumbar fusion have previously not been demonstrated by RCTs. The objectives of this study were, to determine whether lumbar fusion in the long term accelerates degenerative changes in the adjacent disc and whether this affects the outcome, by using a prospective randomised design. A total of 111 patients, aged 18-55, with isthmic spondylolisthesis were randomised to exercise (EX, n = 34) or posterolateral fusion (PLF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(130 citation statements)
references
References 49 publications
2
124
3
1
Order By: Relevance
“…In a prospective clinical study, Ekman et al [24] found that postoperative adjacent segment degeneration occurred in all the patients receiving decompressive laminectomy and posterior fusion with fixation, and that its incidence was significantly higher than that in patients not undergoing decompressive laminectomy. They speculated that decompressive laminectomy was a risk factor for adjacent segment degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective clinical study, Ekman et al [24] found that postoperative adjacent segment degeneration occurred in all the patients receiving decompressive laminectomy and posterior fusion with fixation, and that its incidence was significantly higher than that in patients not undergoing decompressive laminectomy. They speculated that decompressive laminectomy was a risk factor for adjacent segment degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of ASD is low in the great majority of cases [2,[6][7][8]. Cauda equina syndrome is a very unusual onset of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the prevalence of degenerative changes in patients for whom fusion has been prescribed, but not performed, is uncertain. A recent prospective randomized study [8] comparing the effect of fusion with natural history in isthmic spondylolisthesis suggests that laminectomy and fusion accelerate degeneration of the adjacent segment. However, the prevalence of severe ASD is low and the effect on clinical outcome limited.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Shalabi [22] adjacent segment degeneration was considered of prime importance and proved to be a factor in outcome. Compared to PLF only, PLF+ PLIF/TLIF were statistically significantly associated with a greater correction of spondylolisthesis.…”
Section: Follow Upmentioning
confidence: 99%